(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Sri Aurobindo the sage of twentieth century India was one of the prominent leaders of Indian National Movement. He longed for the freedom of soul, so the concept of freedom from Britishers appeared a minor task compared to ultimate liberation of the soul. His philosophy though meant to make individual towards spiritualism, he proceeded with a different perspective.